Heliconiaceae endémicas del Perú - León, Blanca (2006)
The Heliconiaceae are represented in Peru by one genus, Heliconia, and 35 species (Brako & Zarucchi, 1993), all herbs. Here we recognize four endemic species, one of which was assigned an IUCN threat category. These taxa generally occupy the understory of the lower limits of the Humid Premontane Forest region, between 670 and 1200 m elevation. Only one of Peru’s four endemic species has been registered to date in a protected area.